Detection of citrus psorosis virus by RT‐qPCR validated by diagnostic parameters - Simeone, Melina; Gomez, Claudio Andres; Bertalmío, Ana; Ruiz, Esperanza; Hauteville, Claudia; Godoy Suarez, Laura Magdalena; Tito, Blas Alfredo; García, María Laura (Wiley, 2021)
Citrus psorosis virus (CPsV) is the causal agent of psorosis, an important disease of citrus. Sanitary and certification programmes helped reduce disease damage caused by psorosis and other graft‐transmissible diseases in many citrus‐growing regions. For quarantine and certification programmes, most of these diseases are currently diagnosed using biological indexing (BI) on sensitive indicator plants. In the case of citrus psorosis, CPsV can be detected by molecular methods such as quantitative reverse transcription PCR (RT‐qPCR), which is cheaper and faster than BI, but sensitivity, reliability, and reproducibility of both procedures have not been compared so far. In this work, 128 plants from Argentina and Uruguay were analysed using BI and CPsV detection by the RT‐qPCR assay. Almost perfect agreement between both diagnostic procedures and sensitivity, specificity, and estimated likelihood ratios indicate that RT‐qPCR is equivalent to BI for citrus psorosis diagnosis, thus providing confidence in the quick diagnostic procedure to monitor the sanitary status of citrus trees.